Effect of UV radiation on postharvest conservation of blueberries - Campero, Eliana Vanesa; Barrionuevo, Maria Julia; Marigliano, Ana Clelia Gomez (European Journal of Chemistry, 2023)
The objective of this work is to determine the variation in the nutritional and quality characteristics of blueberries subjected to UV radiation. Blueberries of the variety (JEWEL) provided by Tierra de blueberries, Oran, Monteros, Tucuman were used. The parameters analyzed were variations of the color and content of polyphenols by HPLC and UV-vis. Polyphenols determined by HPLC were: delfinidin-3-galactoside, delfinidine-3-glucoside, cyanidin-3-galactoside, delfinidin-3-arabinoside, cyanidin-3-glucoside, petunidin-3-galactoside, cyanidin-3-arabinoside, petunidin-3-glucoside, peonidin-3-galactoside, petunidin-3-arabinoside, malvidin-3-galactoside and malvidin-3-glucoside. From the results obtained, it is concluded that the polyphenol content varied in the irradiated fruits and in the untreated fruits as a function of time, with the values being closest to the initial time value (control) in the case of irradiated fruits. There were no appreciable differences in color change due to irradiation. At time 0, the color difference in the whole fruit between the treated sample (IFC0) and the standard (NFC0) gave ΔE* values equal to 2.06. After 3 days, the color difference was 3.08 for the natural sample and 6.06 for the treated sample. For this reason, it is considered that irradiation of blueberries is a very appropriate method for conservation, maintaining the nutritional and quality characteristics of blueberries.